1976-77 ネン カキ ニ オケル ナンキョク マクマードオアシス ノ エンコ ノ エイヨウ エンルイ - 松本, 源喜; マツモト, ゲンキ; 田中, 良樹; タナカ, ヨシキ; 鳥居, 鉄也; トリイ, テツヤ; Matsumoto, Genki; Tanaka, Yoshiki; Torii, Tetsuya (1982)
P(論文) 1976-77年のフィールドシーズンに南極のロス島, ロイド岬のホーム湖, ドライバレー地域のライト谷のバンダ湖, テイラー谷のボニー湖およびピアス谷のジョイス湖の栄養塩類の研究を行った。その結果ホーム湖のPO_4P濃度は非常に高く, 湖の周辺のアデリーペンギンおよび盗賊カモメの排泄物の影響が著しいことが推察された。バンダ湖およびボニー湖における栄養塩類の鉛直分布のパターンは, 一般に従来の報告と同様でかなり安定していることが確認された。さらに今回初めて調査したジョイス湖にも高濃度のNO_3-NおよびNH_4-Nが検出され, この地域の湖の窒素化合物の濃度が一般に高いという特徴と矛盾しないことが判明した。しかしながら, ボニー湖におけるNH_4-N濃度は, 従来の報告と著しく異なり, 高塩分濃度におけるPO_4-Pの測定とともに, 分析方法の検討がさらに望まれる。 In the 1976-77 austral summer, the distribution of nutrient matters was studied for the waters of Home Lake at Cape Royds of Ross Island, Lake Vanda in the Wright Valley, Lake Bonney in the Taylor Valley and Lake Joyce in the Pearse Valley in the dry valleys of Victoria Land in the Antarctic. High concentration of PO_4-P was found in Home Lake, reflecting presumably the influence of the excretions of the Adelie penguin and the skua around the lake. In general, the vertical distribution pattern of nutrient matters in Lakes Vanda and Bonney was similar to those revealed by the previous studies, although the contents of NH_4-N in the lakes were considerably different from those of the previous works. In addition, high contents of inorganic nitrogen components (NO_3-N and NH_4-N) were found in Lake Joyce. This result is consistent with that inorganic nitrogen components in the lakes of the dry valleys are generally abundant. These nitrogen components were thought to be supplied by glacial meltwater and from lake sediment. However, the studies on the analytical methods should further be required for the determination of NH_4-N and PO_4-P in highly saline waters. departmental bulletin paper